2020
DOI: 10.1111/jan.14347
|View full text |Cite
|
Sign up to set email alerts
|

The intention to undertake physical activity in pregnant women using the theory of planned behaviour

Abstract: AimTo identify the intention of Chinese pregnant women to undertake physical activity (PA) using the theory of planned behaviour.DesignA cross‐sectional survey.MethodsFrom April – October 2017, a cross‐sectional questionnaire was completed by 746 pregnant women from the Health Birth Cohort in Wuhan, China. The theory of planned behaviour variables as well as sociodemographic characteristics was recorded, and the Pregnancy PA Questionnaire was together used to assess their PA during pregnancy.ResultsOnly 11.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…This study explored the correlation between TPB constructs and PA, and the moderating role of MT in PA the intention-behavior gap among college students and wage earners. The TPB constructs could be relevant in explaining the variance of PA intentions, with 46.5% among college students and 38.3% among wage earners, respectively, which was consistent with previous studies (Armitage, 2005;Conner et al, 2011;Rhodes and Bruijn, 2013;Gucciardi, 2015;Hannan et al, 2015;Stolte et al, 2017;Xu et al, 2018;Wang and Zheng, 2020;Zhu et al, 2020). This study also found the different contribution of TPB constructs on intention among college students and wage earners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study explored the correlation between TPB constructs and PA, and the moderating role of MT in PA the intention-behavior gap among college students and wage earners. The TPB constructs could be relevant in explaining the variance of PA intentions, with 46.5% among college students and 38.3% among wage earners, respectively, which was consistent with previous studies (Armitage, 2005;Conner et al, 2011;Rhodes and Bruijn, 2013;Gucciardi, 2015;Hannan et al, 2015;Stolte et al, 2017;Xu et al, 2018;Wang and Zheng, 2020;Zhu et al, 2020). This study also found the different contribution of TPB constructs on intention among college students and wage earners.…”
Section: Discussionsupporting
confidence: 91%
“…Many international studies (Ajzen, 2001;Armitage, 2005;Rhodes and Bruijn, 2013;Maccann et al, 2015;Stolte et al, 2017;Cheng et al, 2019), as well as studies in China (Xu et al, 2018;Wang and Zheng, 2020;Zhu et al, 2020) found that TPB variables could explain the variation of behavioral intention, with attitudes and PBC making a greater contribution than SN to the PA intention of an individual (Li, 1999;Feng and Mao, 2014;Gucciardi, 2015;Hannan et al, 2015;Wang and Zheng, 2020). Some studies also used TPB to promote PA (Valerie et al, 2019;Marashi et al, 2020;Sanaeinasab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, MTM accounted for a moderate amount of variance, which indicates that it is a useful theory to explain PA behavior in Chinese pregnant women. The percentage variance predicted by both models is similar to what has been observed in earlier studies conducted with the theory of planned behavior, social cognitive theory, and the health belief model [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, we found no differences for vigorous PA, which can be explained by the almost total absence of records of vigorous PA in our sample. Physiological changes in pregnancy often make vigorous PA unviable [46]. In addition, clinicians usually recommend light aerobic activities for pregnant women such as light walking.…”
Section: Discussionmentioning
confidence: 99%